Hypertension Associated with Poor Sleep Quality in The Elderly Population in Batu City - Siti Roziah Ria Famuji; Abdul Malik Setiawan; Achdiat Agoes (Journal of Health Science and Prevention, 2021)
Hypertension affects approximately 26% of the adult population and it is a leading cause of death in up to 13.5% worldwide. Hypertension is a disease with the highest prevalence in Indonesia, so good treatment and prevention are needed. Several studies suggest that there is a correlation between hypertension risk factors and the disturbance of sleep quality. Therefore, it is necessary to develop preventive and promotive efforts to obtain optimum blood pressure in patients with hypertension to avoid complications or even death. This study aims to find out the correlation between sleep quality and the value of blood pressure in the elderly ?60 years old in Batu City. A cross-sectional study was conducted in Batu City in 2020. Stratified random sampling was performed to select the respondents. A validated PSQI questionnaire and sphygmomanometer were used to assess sleep quality and blood pressure, respectively. A Chi-Square test was used to test the hypothesis. There were 391 respondents involved in this study. Most of the respondents have poor sleep quality, 205 respondents (52,43%) of which 41 respondents (20%) have normal blood pressure, and 164 respondents (80%) have high blood pressure. The statistical analysis shows a significant correlation (p=0,000) between sleep quality and blood pressure. In conclusion, hypertension is associated with poor sleep quality in the geriatric population in Batu City.